Walking Analysis Using the Angles around the Midpoint between Print Length and Toe Spread by Four Different Color Footprints and SFI in Sciatic Nerve-Injured Rat Model Treated With Curcumin - Ria Margiana (Journal of Global Pharma Technology, 2016)
SFI, the sciatic function index, has been applied as an evaluation method in walking analysis over a long period. It is a method that addresses the functionality of nerves using footprints during walking analysis. Other techniques developed previously make use of one-color ink. The method has difficulties in interpretation due to footprints mingled among the mice specimen's four legs. There exists a possibility of the rats not walking straight, and this leads to overlapping, and the result is complicated measurements. SFI, as a method, entails the application of a mathematical formula that is special. Researchers have questioned this method since it is affected by muscles' contraction, automatic mutilation, and rat motion speed. During this study, the idea is to use four different colors, allowing easier and faster interpretation of the footprints results. Moreover, the study will also modify tools based on the already existing available tools in pre-existing literature. The modified tool gives a measurement of print leg denoted as PL, toe spread TS, and inter- toe spread IT’S, all belonging to the SFI component. The tool's validity and reliability are essential when applied in the measurement of components used in the functional analysis of nerves. Confirmation from the study is that results from SFI and TOA (toe out of angle) all describe footprint. Toe out of angle is an essential measurement in the walking analysis as it has an impact on the alteration of abduction-adduction as well as the internal-external navigation of the hind legs. The study will help develop a method that assesses nerves' functional analysis using the sciatic functional analysis and total out of angle spread. The angle at the intersection point of the print length and the toe spread. Keywords: SFI, TOA and ITS.